Multi-tracer approach to characterize domestic wood burning in Athens (Greece) during wintertime. (January 2017) - Fourtziou, L.; Liakakou, E.; Stavroulas, I.; Theodosi, C.; Zarmpas, P.; Psiloglou, B.; Sciare, J.; Maggos, T.; Bairachtari, K.; Bougiatioti, A.; Gerasopoulos, E.; Sarda-Estève, R.; et al.
Abstract: During the last years the atmosphere of the Great Athens Area (GAA) and other Greek cities is burdened from extended residential biomass burning for heating purposes. In this work, a series of near real-time and off-line biomass burning tracers are analyzed during intense wood burning events in Athens. The measurements were conducted at an urban background site located in the center of Athens, and in the heart of wood burning activities (winter 2013–2014). The measured tracers include high resolution measurements of non-sea salt potassium (nss-K + ), wood burning black carbon (BCwb ), the m/z 60 fragment associated with levoglucosan and monosaccharide anhydrides (levoglucosan, mannosan and galactosan) determined on selected filter samples. The suitability of these tracers was evaluated when the prevailing meteorological conditions with low dispersion and deposition mechanisms (low wind speed, absence of precipitation) were associated with high biomass burning emissions at nighttime. During the severe smog periods, the levels of K +, BCwb, m/z 60 and levoglucosan were up to 2.2 μg m −3, 12.5 μg m −3, 3.4 μg m −3 and 8.6 μg m −3, respectively, higher by a factor of at least two, relatively to the non smog periods due to biomass burning. Correlations between biomass burning tracers as well as between monosaccharide anhydrides provided information about the type of material and wood being burned. Highlights: High temporal resolution measurements were deployed during wintertime in Athens to track and identify a number of different biomass burning tracers. Biomass burning tracers such as non sea salt potassium (nss-K + ), black carbon (BCwb ), the organic fraction m/z 60 and levoglucosan were monitored. The enhanced levels of chloride (Cl − ) could provide evidence of combustion of inappropriate materials being used as fuel. Sodium (Na + ) was also shown to be an alternative combustion tracer. The significant correlation between PM2.5 and levoglucosan, indicated that wood burning could be responsible for PM2.5 higher than 45 μg m −3 .